Is it really an abscess? An unusual case of metastatic stromal cell sarcoma of the prostate - Wickramasinghe, Shehan (Int J Surg Case Rep, 2015)
INTRODUCTION: Prostatic stromal sarcomas account for about 0.1% of all prostatic malignancies. Local recurrence into bladder, seminal vesicles and rectum has been documented. Distal metastasis, has so far only been reported in lung and bone. PRESENTATION OF CASE: We report the case of a 42 year old man with a subcutaneous metastatic deposit of a prostatic stromal cell sarcoma 5 years after radical prostatectomy. Additional staging with CT- and PET-scan showed lymph node involvement in the neck and left axilla. A core biopsy of the skin lesion was undertaken, of which the histology revealed a low grade spindle cell tumour that was morphologically identical to a previously diagnosed prostatic stromal sarcoma. DISCUSSION: In literature distant metastases to the lung and bone have been documented before. This is the first documented case of a subcutaneous metastasis of prostatic stromal cell sarcoma. CONCLUSION: The preferred treatment for prostatic stromal cell sarcoma is surgery by radical prostatectomy or cystoprostatectomy. There is currently not enough literature on the topic to elucidate the role of chemo- or radiotherapy in loco-regional or distant spread.